INTRODUKSI TEKNIK PROSES, TEKNIK PENGEMASAN DAN APLIKASI ENZIM PEKTINASE PADA SARI BUAH JAMBU MERAH DI KELOMPOK TANI CANDI MAKMUR DAN UD. PUTRA JAMBU KECAMATAN NGARGOYOSO KABUPATEN KARANGANYAR JAWA TENGAH [INTRODUCTION PROCESS AND PACKAGING PROCESS WITH PECTINASE ENZYME APPLICATION ON RED GUAVA FRUIT JUICE OF KELOMPOK TANI AND UD. PUTRA JAMBU NGARGOYOSO, KARANGANYAR-CENTRAL JAVA] - Esti Widowati; Adhitya Pitara Sanjaya; Wisnu Adisukma (Jurnal Sinergitas PKM & CSR, 2017)
Red guava fruit is one of superior fruit in Karanganyar regency especially subdistrict of Ngargoyoso. Kelompok Tani Candi Makmur and UD. Putra Jambu has few processed products of red guava fruit since 2005. Red guava fruit juice has not product of this UKM. Readiness of 375 tones/year of red guava fruits only processed as ice cream, stick, paste, kacang nyelip and peyek of red guava leaves. Limitedness of process and packaging process is the main obstruction of diversification of red guava fruit products. Process and packaging process with pectinase enzyme application were introducted by IbM team. Enzyme were used to clarify fruit juice (reduce viscosity and turbidity and increase yield) in order to ease filtration process. Process technique was  appropriate to GMP standart. Introduction included packaging machine, cup sealer and pasteurization to ensure safe products. Product marketing management was improved by new marketing atribut and economic analysis of new products. This effort could increase turnover of UD. Putra Jambu (PUJA) and kelompok tani candi makmur also reinforce economic of Karanganyar regency.